HAVE WE MISCONSTRUED CHRIST’S PRIESTLY AND KINGLY WORK? A Discussion on Analytic and Exegetical Christology - Devina Benlin Oswan (Scriptura Indonesia, 2022)
Within the framework of traditional Christology, the most common interpretation of Christ’s three-fold office is that Christ’s work as our High Priest culminated on the cross as He suffered divine wrath and judgment, while His kingly rule began at His resurrection and ascension. However, with respect to the priestly role, David Moffitt challenges this common understanding and argues that, based on a careful reading of the Epistle to the Hebrews, Christ’s atoning sacrifice ultimately took place during His ascension. Complementing Moffitt’s account, I argue that Christ’s kingly work climaxed in His death on the cross. Using the tools of analytic method, I shall analyze 2 Chronicles 33:1-20 and offer an interpretation to support my argument. If Moffitt’s and my account is Scripturally tenable, it is safe to conclude that traditional Christology has mistakenly reversed Christ’s priestly and kingly role.